Pengaruh Pembengkokan Terhadap Kekuatan Baja Sruktur Tulangan Beton Di Lingkungan Air Gambut - Kana Sabatul Ikhwan; M Dalil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Concrete reinforcement steel bar when it began ordering from manufacturers and further functionalized into the building structure experience bending process to ease the transportation activity or while loading and unloading is not willful bent. Environmental conditions also affect the physical and mechanical condition of the reinforcement steel bar. From the many environmental conditions of corrosion, the selected scope is the peat water as a characteristic geographical conditions in Riau Province. The research methodology is testing experimentally. Concrete reinforcement steel bar is bent on angle (α) 20o, 40o, 60o, 80o, 100o, 120o, 140o, 160o, and 180o. There are two groupings of each bending specimens, they are soaked in the peat water and not soaked in the peat water. Then the specimens is straightened for tensile testing. The average tensile strength and ductility of reinforcing steel bar increase varies depending on the bending angle when compared to normal reinforcement steel bar. The percentage of elongation decreased due to the bending depends of bending angle. Meanwhile, due to bending and soaked in the peat water, the tensile strength was increased but not exceeding the sample group were not soaked and the value of elongation decreased lower than the reinforcing steel bar that is not soaked.Keywords: Bending, Steel bar, Peat Water, Strength